Genetic diversity of the rice blast fungus in a disease nursery in Colombia - Levy, M.; Correa Victoria, Fernando J.; Zeigler, Robert S.; Xu, S; Hamer, JE (Scientific Societies, 1993)
We determined DNA fingerprints and pathotypes on international differentials for 151 isolates of the rice blast fungus Pyricularia grisea that were collected from 15 rice cultivars at a blast disease breeding nursery in Santa Rosa, Colombia. The pathogen population expressed an extraordinarily high number (39) of pathotypes. DNA fingerprinting, using the P. grisea repetitive DNA sequence MGR586, identified 115 haplotypes that were partitioned into six discretely distinct genetic lineages. The mean genetic similarity within lineages was high, ranging from 92 to 98%. The mean similarity between lineages ranged from 37 to 85%. Each lineage was associated with a specific subset of cultivars and expressed a generally nonoverlapping subset of pathotypes. Typically, the pathotypes within a lineage had a closely related infection spectrum, differing by single compatibility differences on a particular subset of the international differentials. The cultivar and pathotype associations indicated that the lineages express historically divergent virulence spectra. MGR-DNA fingerprint analysis also deciphered the lineage associations of 31 isolates whose pathotypes could not be scored, i.e., the isolates were avirulent on all international differentials. MGR-DNA fingerprint analysis provides the genealogical framework for evaluating pathogen variation that is essential for understanding disease epidemiology and pathotype evolution. This kind of analysis may be particularly useful for selecting germ plasm sources for more durable blast-resistance breeding.